1994
DOI: 10.1002/hrdq.3920050103
|View full text |Cite
|
Sign up to set email alerts
|

Management development programs: The effects of management level and corporate strategy

Abstract: In this study of 155 organizations, the relationship between management development programs, managerial level, and organizational strategy was examined. Limited support was established for Katz5 theory about skill requirementsfor managers (1 974). Greater emphasis was placed on technical shills at lower management levels and on entrepreneurial skills at senior management levels. A relationship between corporate strategy and the focus of management development programs also was found. Although organizations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…This measurement is an adaptation of the training effort indicator used by Becker and Huselid (), which has been included in their questionnaires to measure HR strategy. This is equivalent to training and development content being measured as the level of emphasis‐focus that the organization places on each content (see Blakely, Martinec, & Lane, ).…”
Section: Methodsmentioning
confidence: 99%
“…This measurement is an adaptation of the training effort indicator used by Becker and Huselid (), which has been included in their questionnaires to measure HR strategy. This is equivalent to training and development content being measured as the level of emphasis‐focus that the organization places on each content (see Blakely, Martinec, & Lane, ).…”
Section: Methodsmentioning
confidence: 99%
“…Por tanto, la teoría neoclásica no identifica ni explica adecuadamente el comportamiento o factores que dan la definición de desarrollo económico regional o procesos de desarrollo económico. Para complementar, de acuerdo a (Blakey, Lee, & Lane, 1994) define desarrollo económico regional como:…”
Section: Teoría Neoclásica Del Desarrollo Regionalunclassified
“…In the course of their research into the priorities that development areas should receive in management development programs Blakely, Martinec and Lane (1994) found that human relations are equally important for top, middle and lower management. Rashid and Dar (1994) support this by stating that managers can satisf y their subordinates' basic needs for acknowledgement and appreciation by listening and communicating effectively.…”
Section: Socialmentioning
confidence: 99%